A pinecone-inspired hierarchical vertically aligned nanosheet array electrode for high-performance asymmetric supercapacitors. Issue 44 (1st November 2017) - Huang, Jun; Wei, Junchao; Xu, Yazhou; Xiao, Yingbo; Chen, Yiwang
Abstract : A pinecone-inspired hierarchical CNFs/NiCo2 S4 @PPy electrode was elaborately engineered to achieve excellent electrochemical performance due to the favorable structural design. Abstract : While various structures of NiCo2 S4 are well investigated for supercapacitors, it is extremely challenging to achieve high capacitance of NiCo2 S4 by engineering favorable architecture. Here, we have developed a pinecone-inspired supercapacitor electrode composed of vertically aligned NiCo2 S4 nanosheet arrays supported on electrospun carbon nanofibers (CNFs) with polypyrrole (PPy) uniformly wrapped on each nanosheet surface to boost the pseudocapacitive performance. Taking advantages of the high capacitance of vertical NiCo2 S4 nanosheets and the conductive wrapping of PPy, the hybrid electrode exhibits high specific capacitance (2961 F g −1 at 1 A g −1 ) with excellent cycling stability (99.85% capacitance retention after 5000 cycles). The asymmetric supercapacitor (ASC) fabricated using the CNFs/NiCo2 S4 @PPy nanosheet arrays as the positive electrode and CNFs/MoS2 nanosheets as the negative electrode demonstrates outstanding electrochemical performance for practical energy storage applications. The ASC shows excellent maximum energy density of 37.15 W h kg −1 at the power density of 598.80 W kg −1 in an aqueous electrolyte and 44.45 W h kg −1 at the power density of 698.60 W kg −1 in a quasi-solid state gel electrolyte with robust long-term cycling stability.